Two alternating structures of the HIV-1 leader RNA. - Huthoff, H (2001)
In this study we demonstrate that the HIV-1 leader RNA exists in two alternative conformations, a branched structure consisting of several well-known hairpin motifs and a more stable structure that is formed by extensive long-distance base pairing. The latter conformation was first identified as a compactly folded RNA that migrates unusually fast in nondenaturing gels. The minimally required domains for formation of this conformer were determined by mutational analysis. The poly(A) and DIS regions of the leader are the major determinants of this RNA conformation. Further biochemical characterization of this conformer revealed that both hairpins are disrupted to allow extensive long-distance base pairing. As the DIS hairpin is known to be instrumental for formation of the HIV-1 RNA dimer, the interplay between formation of the conformer and dimerization was addressed. Formation of the conformer and the RNA dimer are mutually exclusive. Consequently, the conformer must rearrange into a branched structure that exposes the dimer initiation signal (DIS) hairpin, thus triggering formation of the RNA dimer. This structural rearrangement is facilitated by the viral nucleocapsid protein NC. We propose that this structural polymorphism of the HIV-1 leader RNA acts as a molecular switch in the viral replication cycle.